Antioxidant Compounds in the Treatment of Alzheimer's Disease: Natural, Hybrid, and Synthetic Products. (21st February 2023) - Hatami, Maryam; Mortazavi, Mojtaba; Baseri, Zahra; Khani, Batool; Rahimi, Mehdi; Babaei, Sahar
Abstract : Alzheimer's disease (AD) which is associated with cognitive dysfunction and memory lapse has become a health concern. Various targets and pathways have been involved in AD's progress, such as deficit of acetylcholine (ACh), oxidative stress, inflammation, β -amyloid (A β ) deposits, and biometal dyshomeostasis. Multiple pieces of evidence indicate that stress oxidative participation in an early stage of AD and the generated ROS could enable neurodegenerative disease leading to neuronal cell death. Hence, antioxidant therapies are applied in treating AD as a beneficial strategy. This review refers to the development and use of antioxidant compounds based on natural products, hybrid designs, and synthetic compounds. The results of using these antioxidant compounds were discussed with the given examples, and future directions for the development of antioxidants were evaluated.